The Effect Of Using Pure Coconut Oil On Toddlers Against Ringworm (Miliaria) In The Kerna Area Of The Telaga Dewa Health Center Kota Bengkulu City 2025 - Febyana Febyana; Diyah Tepi Rahmawati; Meita Tria Saputri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This Study to determine the effect of Virgi Coconut Oil (VCO) on reducing prickly heat (miliaria) in toddlers at the working area of telaga dewa Public Health Center, Bengkulu City in 2025. The research employed a pre-experimental design with a one-group pretest-posttest approach, involving 14 toddlers who met the inclusion and exclusion criteria. Data were collected through direct observation using a screening sheet, and VCO was applied twice daily (morning and evening) for six consecutive days on the affected skin areas. The results showed that before the intervention, 78.6% of respondents experienced prickly heat, whereas after the intervention only 14.3% remained affected. Statistical analysis using the McNemar test obtained a p-value of 0.001 (p < 0.05), indicating a significant effect of VCO in reducing prickly heat in toddlers. In conclusion, Virgin Coconut Oil can be considered a safe, natural, and easily accessible non-pharmacological alternative to improve skin health and reduce prickly heat in toddlers. However, further studies with larger sample sizes and control groups are recommended to strengthen these findings.